Poststrukturalisti križem rok opazujejo svet v plamenih - Mehaffy, Michael W. (Urbani izziv, 2012)
We critique the current crisis for the environmental design professions: facing urgent ecological, social and economic imperatives, key leadership has become mired in the confusions of do nothing postmodernist artistic doctrine. The result is a self made state of paralysis, leaving the egregious mistakes of the past to be endlessly repeated, while it only matters that they are cloaked in ever more aesthetically extravagant artistic garb. We argue that this self excusing paralysis arises because, under a poststructuralist infatuation with ambiguity, multiplicity and constructed meaning, an effective shared framework to address the urgent challenges of the built environment becomes impossible. This paralysis is rewarded, however, because it serves narrow economic interests, which are happy to find rationalisations for projects that might otherwise be rejected as of inferior quality. We conclude with the hopeful observation that the ingredients of such a framework are indeed emerging from the biological sciences and other fields. However, to make use of them, we argue, professionals must learn to critique, and finally to dispense with, the misapplications of non productive forms of thinking, a number of which we specify herein. We hope this paper will serve as one small step on that important path.
Keywords: architectural culture; architecture; arhitektura; arhitekturna kultura; bivalno okolje; environmental design criticism; kritika okoljskega načrtovanja; poklicna odgovornost; postmodernism; postmodernizem; poststructuralism; poststrukturalizem; professional responsibility; prostorsko planiranje; spatial planning; urbanism; urbanistično planiranje; urbanizem